About identities and struggles: interview with ana maría spadafora (2011)
Anthropologist Ana María Spadafora describes the current situation of indigenous communities in Argentina. She explains the meaning of “being Indian” and how processes of ethnic re-emergence have taken place in Argentina and elsewhere in the continent. The articulation between Positive Law and indigenous world view, and the effects of globalization on ethnic minorities are some of the issues covered.